An In-Silico, In-Vitro and In-Vivo Combined Approach to Identify NMNATs as Potential Protein Targets of ProEGCG for Treatment of Endometriosis - Hung, Sze Wan; Liang, Bo; Gao, Yating; Zhang, Ruizhe; Tan, Zhouyurong; Zhang, Tao; Chung, Pui Wah Jacqueline; Chan, Tak Hang; Wang, Chi Chiu (Frontiers in Pharmacology, 2021)
Endometriosis is defined as endometrial tissues found outside the uterine cavity. ProEGCG is a prodrug of Epigallocatechin gallate (EGCG), a potent polyphenol found in green tea. It inhibits the development of endometriotic lesions of mouse model in vivo, with higher efficacy and more remarkable anti-oxidative ability than EGCG. Our study aims to identify the molecular binding targets and pharmacological actions of ProEGCG in treating endometriosis. Protein target interaction study is essential to fully characterize the mechanism of actions, related therapeutic effects, and side effects. We employed a combined approach, starting with an in silico reverse screening of protein targets and molecular docking, followed by in vitro cellular thermal shift assay (CESTA) to assess the stability of protein-small molecule complexes. Then microarray and immunostaining of endometriotic lesions in mice in vivo confirmed the molecular interaction of the selected targets after treatment. Our study identified enzymes nicotinamide nucleotide adenylyltransferase (NMNAT)1 and NMNAT3 as protein targets of ProEGCG in silico and in vitro and were overexpressed after ProEGCG treatment in vivo. These findings suggested that participation in nicotinate and nicotinamide metabolism potentially regulated the redox status of endometriosis via its antioxidative capacities through binding to the potential therapeutic targets of ProEGCG.